Bridging the ICD11 and the DSM-5 personality disorders classification systems: The role of the PID5BF + M - Pires, Rute (2023)
Introduction: In both the ICD-11 Classification of Personality Disorders and the DSM-5 Alternative Model of Personality Disorders (AMPD) personality disorders (PD) are characterized by impairments in self- and interpersonal functioning which distinguish the various levels of dysfunction. Moreover, pathological traits are used by these classification systems to define the stylistic expression of personality dysfunction. Negative affectivity, detachment, antagonism/dissociality, and disinhibition feature as trait domains in each of these models. However, there are also differences between the two models, namely, in the psychoticism domain, which does not feature as a personality trait domain in the ICD-11, and in the anankastia domain, corresponding to compulsivity in the DSM-5, which was removed from the final AMPD model. Furthermore, facets are acknowledged by the DSM-5 within each trait domain, while this does not occur in the ICD-11. In view of the similarity between these classification systems, their harmonization would be beneficial for the clinical profession. With this goal in mind, the PID5BF + M, an algorithm that assesses the DSM-5 and ICD-11 six trait domains and 18 facets, was developed and has proven to adequately characterize the ICD-11 trait domains by means of DSM-5 trait facets. Methods: The current study compares a community sample (N = 280, Mage = 48.01, 53.2% females) with a PD sample (N = 131, Mage = 42.66, 45.0% females) along with the PID5BF + M, the LPFS-SR and the PID-5. Given that the PID5BF + M total can be seen as a measure of the level of personality dysfunction, strong relations between the PID5BF + M total and the LPFS-SR total are expected. Strong relations between the trait specifiers measured by the PID5BF + M and the PID-5 are also expected. Finally, the community and clinical samples are expected to differentiate by means of the dimensions assessed through the three aforementioned measures. The Spearman rank-order correlation coefficient was used to measure the strength and direction of associations between the PID5BF + M total and the LPFS-SR total and between the PID5BF + M and the PID-5 traits. Group differences were explored using the Mann–Whitney U test for independent samples. Results: As expected, there were strong, significant, and positive relations between the measures. Furthermore, higher scores were observed in all the variables for the PD group against the community group. Discussion: Although this study has limitations, its findings sustain that the PID5BF + M has potential to assess the severity of personality disfunction and to characterize the stylistic features of PD as they are conceived by both the ICD11 and the DSM-5. Although more research is needed regarding the convergent validity of the PID5BF + M, this new test contributes to the harmonization of both systems and to parsimony in the assessment of PD, which is the main objective of clinical practice.